The effect of agrivoltaic system on nutrient content, yield, and water productivity of potatoes - Witwit, Israa M. T.; Al-agele, Hadi A.; Higgins, Chad W. (Frontiers in Horticulture, 2025)
Integrating innovative technologies such as agrivoltaic systems, improving water use efficiency, and adopting climate-smart agricultural practices can help ensure that farming systems are resilient, resource-efficient, and capable of feeding future generations. This study aims to investigate the growth of potato plants both beneath and between simulated solar panels, as well as in a control area. The effects of two levels of deficit irrigation (35% and 50%) and three levels of potassium sulfate fertilizer are examined. Total yield, water productivity, and nutrient analysis of the plants, potatoes, and soil are conducted. The results show that light conditions are the most significant factor (more than irrigation or fertilizer) for most observations. The results show that light conditions are the most important factor (more so than irrigation or fertilizers), with total yields higher (277.9 kg or more than 17 t/ha) at irrigation level (I0.35) and (241.4 kg or more than 15 t/ha) at irrigation level (I0.5) in the partially shaded areas between the solar panels marked as (B). In contrast, the total yield in the light areas (L) was (253.1 kg or more than 16 t/ha) at irrigation level (I0.35) and (232.3 kg or more than 14 t/ha) at irrigation level (I0.5), while the yield in shaded areas (S) was (204.8 kg or more than 13 t/ha) at irrigation level (I0.35) and (191.45 kg or more than 12 t/ha) at irrigation level (I0.5). The decrease in total production in the shade was 26% at irrigation level (I0.35) and 20% at irrigation level (I0.5) compared to the partial-shade area, and 19% at irrigation level (I0.35) and 18% at irrigation level (I0.5) compared to the light area. The results of water consumption (added water) indicated that the amount of water added to plants growing in shade was significantly less than that of plants in partial shade and light at both irrigation levels. The amount of added water in the shade was 3833 m3/ha at irrigation level (I0.35) and 3517 m3/ha at irrigation level (I0.5). In partial shade, it was 3883 m3/ha at irrigation level (I0.35) and 3585 m3/ha at irrigation level (I0.5). In light conditions, it was 3903 m3/ha at irrigation level (I0.35) and 3607 m3/ha at irrigation level (I0.5). The results indicated that water productivity in partial shade and light conditions differed significantly from that of shaded plants at both irrigation levels. Water productivity values in partial shade were recorded at 4.42 kg/m3 at irrigation level (I0.35) and 4.16 kg/m3 at irrigation level (I0.5). Under light conditions, water productivity values measured 4.00 kg/m³ at irrigation level (I0.35) and 3.98 kg/m3 at irrigation level (I0.5). In the shade, water productivity values were 3.30 kg/m3 at irrigation level (I0.35) and 3.36 kg/m3 at irrigation level (I0.5). The increase in water productivity in the interpanel areas suggests that the combination of shading and irrigation contributed to water conservation and reduced evaporation, leading to more efficient water use without compromising overall production. The combination of full shade, 35% irrigation deficit, and low potassium enhances available phosphorus and decreases potassium concentrations in the soil. The discovery that agrivoltaic systems can support healthier soil nutrient dynamics through shading and deficit irrigation is a promising area for future research into sustainable farming practices.